Comparative Performance Of ALOS PALSAR Polarization Bands And Its Combination With ALOS AVNIR-2 Data For Land Cover Classification - Sim, Chong Keat (2012)
Microwave Remote Sensing data have been widely used for land cover classification in our environment. In this study, ALOS PALSAR polarization bands were used to identify land cover features in three study areas in Malaysia. The study area consists of Penang, Perak and Kedah. The aims of this research are to investigate the performance of ALOS PALSAR datasets which are assessed independently and combination of these data with ALOS AVNIR-2 for land cover classification. ASF MapReady program from Alaska satellite Facility Geographical Institute at the University of Alaska Fairbanks was used for the preprocessing of ALOS PALSAR data.